Difficulties faced by vocal students lacking in piano skills / Josephine Jurie Kubu - Jurie Kubu, Josephine (2015)
The purpose of this study was to investigate difficulties face by vocal student without piano skills‘ On the other hand, the study tries to identify the difficulties that vocal students faced without piano skills face when they practice what are the important piano skills every vocal student must have such as what do the difficulties they face during warm up as well as practice their repertoire, Beside it, it also investigates the important of piano among the vocal student in UiTM